Peningkatan Pengetahuan Pencegahan Autoimun Jenis Lupus Eritematosus Sistemik (LES) Melalui Promosi Kesehatan Pada Calon Perawat - Maemunah, Neni; Devi, Hilda Mazarina; Putri, Rona Sari Mahaji (Nursing News : Jurnal Ilmiah Keperawatan, 2025)
Systemic Lupus Erythematosus (SLE) is a complex and systemic autoimmune disease that can affect various organs and tissues in the body. With increasing prevalence and a significant impact on the quality of life of diagnosed individuals, a deep understanding of SLE is essential, especially among healthcare professionals. This study aims to explore the level of knowledge regarding SLE among nursing students, as well as the factors influencing their understanding. A quasi-experimental study was conducted with a one-group pretest-posttest design. The population consisted of 370 with 152 students recruited using incidental sampling. Video, poster, and leaflet as health promotion media, while a separate questionnaire was used to assess the respondents' knowledge before and after the intervention. Data analysis was performed using the marginal homogeneity test. The results showed that nearly half (48.0%) of the respondents had moderate knowledge about the prevention of autoimmune SLE before the health promotion, and the majority (67.1%) had good knowledge after the health promotion. The Marginal Homogeneity test results showed a p-value of 0.000, indicating that there was a significant effect of health promotion on knowledge about autoimmune SLE prevention. Improving nursing students' knowledge of SLE through comprehensive health promotion programs is crucial in encouraging effective preventive behavior. Future researchers are advised to investigate factors that can help in designing more effective educational interventions for patients.